1.13

From The Algorithm Design Manual Solution Wiki
Revision as of 12:18, 1 September 2020 by Algowikiadmin (talk | contribs) (Created page with "The basis case is when <math>n = 0</math><br> :<math>\sum_{i=1}^0 i^2 = 0^2 = 0 </math><br> and using <math>n=0</math> in the formula <math>\frac {n(n + 1)(2 \cdot n + 1)} {6}...")
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search

The basis case is when


and using in the formula you get:


Since these are equal, the basis case is true.


Now, I will show that on the assumption that the summation is true for n, it follows that it is true for


Which should be equal to the formula when :


Back to Chapter 1.